Interfering with S100B–effector protein interactions for cancer therapy. Issue 9 (September 2020) - Wu, Ke-Jia; Wang, Wanhe; Wang, Hui-Min David; Leung, Chung-Hang; Ma, Dik-Lung
Highlights: S100B is overexpressed in various malignant tumors. S100B exerts its biofunctions by physical interactions with other molecules. Interfering with S100B-effector protein interactions is a potential strategy for cancer therapy. Virtual screening is an efficient approach to identify protein–protein interactions inhibitor. Abstract : S100 calcium-binding protein B (S100B) is overexpressed in various malignant tumors, where it regulates cancer cell proliferation and metabolism by physical interactions with other molecules. Interfering with S100B–effector protein interactions is a potential strategy to treat malignant tumors. Although some S100B inhibitors have been discovered by virtual screening (VS), most target the S100B–p53 interaction. Hence, there is scope for the discovery of other S100B–effector protein interaction modulators for malignant tumors. In this review, we provide an overview of S100B–effector protein interaction inhibitor discovery using VS and discuss promising S100B–effector protein interaction targets that permit in silico analysis for drug discovery.